2020
DOI: 10.1634/theoncologist.2019-0967
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Characterization of Estrogen Receptor Status in Metastatic Breast Cancer with 16α-18F-Fluoro-17β-Estradiol Positron Emission Tomography: Meta-Analysis and Recommendations for Integration into Clinical Applications

Abstract: Estrogen receptor (ER) status by immunohistochemistry (IHC) of cancer tissue is currently used to direct endocrine therapy in breast cancer. Positron emission tomography (PET) with 16α-18F-fluoro-17β-estradiol (18 F-FES) noninvasively characterizes ER ligand-binding function of breast cancer lesions. Concordance of imaging and tissue assays should be established for 18 F-FES PET to be an alternative or complement to tissue biopsy for metastatic lesions. We conducted a metaanalysis of published results comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 65 publications
2
102
0
Order By: Relevance
“…Previous studies showed that FES uptake corresponds with ER expression on immunohistochemistry in breast cancer and uterine cancer [ 22 , 23 ]. Compared to immunohistochemical staining, FES-PET has a sensitivity of 0.81 and specificity of 0.86 in breast carcinoma studies [ 24 ]. We could not confirm this correlation in AGCTs, potentially due to the small sample size of the study, the time interval between tissue withdrawal and the FES-PET/CT, and varying ER expression levels between tumor lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that FES uptake corresponds with ER expression on immunohistochemistry in breast cancer and uterine cancer [ 22 , 23 ]. Compared to immunohistochemical staining, FES-PET has a sensitivity of 0.81 and specificity of 0.86 in breast carcinoma studies [ 24 ]. We could not confirm this correlation in AGCTs, potentially due to the small sample size of the study, the time interval between tissue withdrawal and the FES-PET/CT, and varying ER expression levels between tumor lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sex hormone binding globulin local concentrations keep readily releasable pools of steroids available and difficult to measure ( Södergård and Bäckström, 1987 ). However, it is clear that there is a relationship between blood serum and cerebral spinal fluid concentrations of neuroactive steroids and steroids in blood circulation clearly cross the blood brain barrier in both humans and animal models as demonstrated by 16a-18F-Fluoro-17b-Estradiol positron emission tomography ( Khayum et al, 2014 ; Kurland et al, 2020 ). Furthermore, blood serum progesterone and estradiol correlations with human cerebrospinal fluid are relatively rare with one notable study finding positive correlations of 0.731 for estradiol and 0.913 for progesterone ( Bäckström et al, 1976 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lobular breast cancers have long been known to be more occult on imaging in the primary and metastatic setting. Progress has been made with [18F]-fluoro-estradiol (FES) positron-emission tomography (PET) imaging [23,24] and Fluciclovine (18F-FACBC) PET [25] and additional trials are ongoing, including one focused on FES-PET/CT Imaging of ILC (NCT04252859, https://clinicaltrials.gov/ct2/show/NCT04252859, accessed on 6 May 2021).…”
Section: Historic View Of Lobular Carcinoma Is Challenged By New Evidencementioning
confidence: 99%